Sports in American history from colonization to globalization - Gems, Gerald R. PhD; Borish, Linda J. 1961- PhD; Pfister, Gertrud 1945- PhD (Human Kinetics, 2017)
Sports in American History: from colonization to globalization, second edition, journeys from the early American past to the present to give readers a compelling grasp of the historical evolution of American sporting practices. This text provides insights that will allow readers to develop new and alternative perspectives, examine sport as a social and cultural phenomenon, generate a better understanding of current sport practices, and consider future developments in sport in American life. The second edition includes the following enhancements: the final chapter highlights sport in the twenty-first century and gives students an updated view of contemporary sport; expanded content about the progressive era provides students with a clearer understanding of this instrumental period; new "people and places" and "international perspectives" sidebars introduce key figures in sport history and provide students with a global understanding of sport; timelines with major sport and societal events and milestones provide context in each chapter; more than 150 images provide historical authenticity and relate people and events to the accompanying text; chapter objectives and discussion questions help students absorb and apply relevant content; an ancillary suite helps instructors prepare for class with an instructor guide, test package, and presentation package